Opóźniony w czasie masywny krwotok nadnaczyniówkowy po operacji odwarstwienia siatkówki – opis przypadku - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Massive suprachoroidal hemorrhage may occur at surgery, early postoperatively or may be delayed. The authors describe a case of 79-year-old woman, who developed a massive suprachoroidal hemorrhage in 72 hours after retinal detachment surgery. In our case, the main reason of suprachoroidal hemorrhage development was postoperative hypotony and occurence of a lot of factors such hypertension, diabetes, high myopia, pseudophakia, which predispose to hemorrhage. This case is very rare but interesting because of its multifocal pathogenetical mechanism.